Wearable wideband textile coplanar Vivaldi antenna for medical and IoT application - Nurhayati, Nurhayati; Al Gburi, Ahmed Jamal Abdullah; Fahmi, Agam Nizar Dwi Nur; Puspitaningayu, Pradini; Wiriawan, Oce; Raafi’u, Brian; Iskandarianto, Fitri Adi; Varshney, Atul; Johari, Safpbri (The Electromagnetics Academy, 2024)
Wearable technologies will be extremely useful in the future life. This research proposes a textile wideband coplanar Vivaldi antenna constructed from a felt substrate and two distinct types of patches, shieldit, and copper tape integrated with a wearable device. This study also altered the slope of the tapered slot on the antenna’s front and side to see how it affected the bandwidth and directivity antenna performance. An IoT wearable device that was connected to a microcontroller via a DS18B20 body temperature sensor and a MAX30100 sensor for heart rate and oxygen level monitoring was paired with the textile antenna. Based on the simulation findings, it was discovered that a 1 mm thick felt substrate material combined with a copper tape patch produces a workable frequency range of 2.6 GHz to 8.7 GHz, a minimum S11 of −44.93 dB at 3 GHz, and a fractional bandwidth up to 107%. According to the simulation results, the antenna’s side and front tapered slots have an impact on directivity and return loss. Directivity at 3 GHz can be raised by 2.63 dBi, from 1.94 dBi to 4.57 dBi, by varying the Vivaldi antenna form on both sides of the patch. The data from the sensor was successfully conveyed by combining an IoT wearable device with a textile antenna. Thus, we deduce that the textile coplanar Vivaldi antenna is appropriate for Internet of Things applications.